143 The Combination of anti-TIM-3 and anti-PD-1 Checkpoint Inhibitors With Focused Radiation Resulted in a Synergistic Antitumor Immune Response in a Preclinical Glioma Model. Issue Volume 62:Issue CN Supp 1(2015)Supplement 1 (August 2015) - Kim, Jennifer E.; Patel, Mira A.; Mangraviti, Antonella; Velarde, Esteban; Theodros, Debebe; Mathios, Dimitris; Jackson, Christopher Mitchell; Tyler, Betty; Ye, Xiaobu; Brem, Henry; Pardoll, Drew; Lim, Michael
Abstract : INTRODUCTION: Checkpoint molecules like programmed death-1 (PD-1) and T-cell immunoglobulin mucin-3 (TIM-3) act as negative regulators of the immune system and can be upregulated in the setting of glioblastoma multiforme (GBM). Combined PD-1 blockade and stereotactic radiosurgery (SRS) have been shown to improve antitumor immunity and produce long-term survivors in a murine glioma model. However, tumor-infiltrating lymphocytes can express multiple checkpoints (including TIM-3), and expression of 2 or more checkpoints corresponds to a more exhausted T-cell phenotype. Here, we hypothesized that the addition of a second checkpoint-blocking antibody could achieve additive or synergistic antitumor effects. METHODS: C57BL/6 mice were implanted with mouse glioma cell line GL261 transfected with luciferase and randomized into 8 treatment arms: (1) control, (2) SRS, (3) anti-PD-1 antibody, (4) anti-TIM-3 antibody, (5) anti-PD-1 + SRS, (6) anti-TIM-3 + SRS, (7) anti-PD-1 + anti-TIM-3, and (8) anti-PD-1 + anti-TIM-3 + SRS. Overall survival was measured. Brain, cervical lymph nodes, and peripheral blood were harvested on day 21 to assess immune activation. RESULTS: Survival benefits were demonstrated with combined anti-TIM-3 antibody + SRS compared with anti-TIM-3 antibody alone with a median survival (MS) of 92 vs 25 days and overall survival (OS) of 50% vs 0%, respectively ( P < .001 by log-rank Mantel-Cox). Dual blockade with anti-TIM-3 + anti-PD-1 antibody also improved survival compared with TIM-3 blockade alone (MS of 146 vs 25 days, OS 60% vs 0%, respectively, P < .05). Notably, the triple-modality treatment (anti-PD-1 + anti-TIM-3 + SRS) provided a significant improvement in survival compared with all other treatment arms with an OS of 100% by day 146 ( P < .05). Flow cytometry of organs harvested on day 21 showed that, compared with dual-therapy groups, mice treated with the triple-modality treatment had increased tumor infiltration by interferon-gamma+ (IFN-γ) and tumor necrosis factor-alpha+ (TNF-α)-producing CD4 + T cells, as well as IFN-γ+ CD8 + lymphocytes. CONCLUSION: Combining anti-TIM-3 with anti-PD-1 and radiation was synergistic and conferred a significant survival benefit.